2020
DOI: 10.3390/ijms21239124
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid and Carbohydrate Metabolism Are Coordinated to Maintain Energetic Balance during Drought in Sugarcane

Abstract: The ability to expand crop plantations without irrigation is a major goal to increase agriculture sustainability. To achieve this end, we need to understand the mechanisms that govern plant growth responses under drought conditions. In this study, we combined physiological, transcriptomic, and genomic data to provide a comprehensive picture of drought and recovery responses in the leaves and roots of sugarcane. Transcriptomic profiling using oligoarrays and RNA-seq identified 2898 (out of 21,902) and 46,062 (o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 125 publications
1
24
0
1
Order By: Relevance
“…For example, in the reaction of glycine to serine, one of the key enzymes, serine hydroxymethyltransferase (glyA, SHMT, EC 2.1.2.1) catalyzed the mutual conversion of glycine and serine, and provided the activation required for the synthesis of nucleic acids and proteins and the one-carbon metabolism pathway [ 76 ]. SHMT participated in the photorespiration pathway of plant oxygen-containing photosynthetic organisms [ 77 ] and played a vital role in drought [ 78 ], high salinity [ 79 ], high Zn toxicity [ 76 ], and other abiotic stresses. AtSHMT1 was also involved in HCHO glycoassimilation [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the reaction of glycine to serine, one of the key enzymes, serine hydroxymethyltransferase (glyA, SHMT, EC 2.1.2.1) catalyzed the mutual conversion of glycine and serine, and provided the activation required for the synthesis of nucleic acids and proteins and the one-carbon metabolism pathway [ 76 ]. SHMT participated in the photorespiration pathway of plant oxygen-containing photosynthetic organisms [ 77 ] and played a vital role in drought [ 78 ], high salinity [ 79 ], high Zn toxicity [ 76 ], and other abiotic stresses. AtSHMT1 was also involved in HCHO glycoassimilation [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in specific cases, such alterations also help organisms adapt to external stresses, such as in the development of resistance in mycobacteria under rifampicin stress and in the conformational maintenance of reactive oxygen species susceptibility proteins in yeast under oxidative stress conditions . Furthermore, amino acids are involved in the synthesis of metabolic enzymes and act as donor precursors to influence the ATP supply cycle for numerous enzymatic reactions. In conclusion, the strong perturbation of the aminoacyl-tRNA biosynthesis and numerous amino acid synthesis/metabolic pathways revealed an alteration in the global metabolic state of Bifidobacterium strains under LA stress.…”
Section: Discussionmentioning
confidence: 99%
“…For the different sugarcane tissues of SP80-3280 analyzed here, the main metabolic systems that were altered throughout development and in response to changes in the external environments were amino acid metabolism, mostly Phe, Tyr, Trp metabolism; and secondary metabolism, mostly phenylpropanoid metabolism and the metabolism of its upstream precursors and/or downstream products. Previous studies on the effects of abiotic stress on plants such sugarcane and Arabidopsis have reported alterations in amino acid metabolism [ 85 , 86 ]. In sugarcane, during drought stress the carbohydrate metabolism is coordinated with the degradation of amino acids probably to provide carbon skeletons for the tricarboxylic acid cycle maybe facilitating recovery after the stress [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the effects of abiotic stress on plants such sugarcane and Arabidopsis have reported alterations in amino acid metabolism [ 85 , 86 ]. In sugarcane, during drought stress the carbohydrate metabolism is coordinated with the degradation of amino acids probably to provide carbon skeletons for the tricarboxylic acid cycle maybe facilitating recovery after the stress [ 85 ]. Aromatic amino acids such as Phe, Tyr, Trp, are the main amino acids being synthesized under stress conditions [ 86 , 87 ] and these aromatic amino acids serve as precursors for secondary metabolites, such as glucosinolates, alkaloids, and phenylpropanoids, which play important roles in plant development [ 88 , 89 ].…”
Section: Discussionmentioning
confidence: 99%